Polder system water management on non-tidal swamp area based on water balance analysis. Issue 1 (February 2021) - Kartiwa, B; Sutrisno, N; Hamdani, A; Nugroho, W T; Muhardiono, I; Harmanto,; Yani, I; Roland, R; Ismail, I
Abstract: Polder system is the key to manage floods in agricultural non-tidal swamp land. Infrastructures to support polder system integrated management include: regional drainage systems, retention ponds, dikes, pumps and/or gates. Pump requirement in an optimally managed polder system is influenced by the polder area, rainfall, soil, and hydrological characteristic. This article presents water balance models application in determining the number and operational duration of pumps to achieve effective and optimal polder function in controlling floods and inundation during the rainy season. This study was conducted in a palm-oil plantation located in lebak swamp area in Pawalutan, Banjang, Hulu Sungai Utara, during September 2016 to September 2017. Pump units and operation durations were calculated based on estimated inundation volumes depending on the water inlet and water balance. Seepage discharge was estimated using Darcy equation. Result of the recovery test measurements showed hydraulic conductivity value of 4.1x10 −05 ms −1, while the estimated seepage discharge was 8.6 m 3 hr −1 km −1 . The pump requirement analysis indicated the need of 55 pump units with 2, 500 m 3 hr −1 pumping capacity to overcome inundation in the study site with 1, 417 ha inundated area. These pumps were distributed into 9 zones, each with 4 to 10 units.